2020
DOI: 10.34098/2078-3949.37.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Variación en La Concentración De Flavonoides Y Clorofila, Y Cambios en La Morfología Y Anatomía Foliar, Debidos a Radiación Visible (Par) O Ultravioleta (Uva, Uvb) en Baccharis Latifolia

Abstract: Baccharis latifolia es una planta de interés medicinal e industrial con presencia importante de flavonoides en las hojas. El presente estudio se centró en identificar los cambios en flavonoides totales, concentración de clorofilas, crecimiento de la planta y anatomía foliar bajo diferentes longitudes de onda (UVA, UVB y PAR) en condiciones controladas. Se realizaron análisis estadísticos utilizando pruebas no paramétricas Kruskal-Wallis y post hoc Bonferroni. Los resultados sugieren que mejores condiciones par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The correlations of different degrees found between compounds in both plants were weak, especially for total chlorophyll ( P. oleracea ). This might be due to common factors in the secondary metabolite’s synthesis pathway, and in the case of chlorophyll, there is a dependence on foliar anatomy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlations of different degrees found between compounds in both plants were weak, especially for total chlorophyll ( P. oleracea ). This might be due to common factors in the secondary metabolite’s synthesis pathway, and in the case of chlorophyll, there is a dependence on foliar anatomy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baccharis genus plants are used in folk medicine in Bolivia attracting the attention of our research group that studied six Baccharis species: Baccharis latifolia (Enríquez et al, 2018;Loza Almanza et al, 2011), B. papillosa (Escobar et al, 2009;Loza Almanza et al, 2011), B. boliviensis (Calle et al, 2012;2017), B. densiflora previously identified as B. pentlandii (Sotillo et al, 2021;Tarqui et al 2012), B. tola Syn B. santelices (Villagómez et al, 2006) and B. lepthophylla (Almanza et al, 2000;Salcedo Ortiz et al, 2013). In addition, some studies suggested that the concentration of flavonoids in these plants is linked to the UV-exposure (Peñaranda, 2020). B. papillosa, previously identified as B. obtusifolia, reported the presence of phenolic compounds, coumarins, steroids and a sesquiterpene lactones (Escobar et al, 2009;Zdero et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that flavonoids and derivatives of cinnamic acid absorb UV radiation (Calle et al, 2012;Escobar et al, 2009;Nichols and Katiyar, 2010;Peñaranda et al, 2020). Several studies made in Arabidopsis mutants proved that large amounts of flavonoids, anthocyanins and sinapic esters were found in A. mutants tolerant and resistant to UV radiation (Landry et al, 1995;Li et al, 1993).…”
Section: Introductionmentioning
confidence: 99%